Perioperative Antithrombotic Management - Andrianto, Andrianto; Arindanie, Amelia (Indonesian Journal of Cardiology, 2017)
The management of antithrombotic therapy in the perioperative setting is a common problem, balancing haemorrhagic risk with thrombotic risk. High-quality evidence is lacking regarding the optimal approach for patients on oral anticoagulants or antiplatelet agents. The two main issues that need to be considered in perioperative antithrombotic management is the patient’s risk of a thromboembolic event when therapy is interrupted and the risk of bleeding associated with the surgery or procedure. An assessment of these factors will determine the optimal perioperative anticoagulant management approach. The overall objective of this review is to provide a practical approach relating to perioperative management which can be used in everyday clinical practice.   Abstrak Masalah tatalaksana terapi antitrombotik perioperatif yaitu menyeimbangkan risiko perdarahan dan risiko trombosis masih sering dijumpai sehari-hari. Bukti klinis yang kuat mengenai tatalaksana yang optimal dari terapi antikoagulan atau antiplatelet masih sangat sedikit. Dua hal yang perlu dipikirkan dalam tatalaksana terapi antitrombotik perioperatif adalah risiko kejadian tromboemboli ketika terapi antitrombotik dihentikan dan risiko perdarahan akibat tindakan pembedahan yang dilakukan. Penilaian faktor-faktor tersebut akan menentukan pendekatan yang optimal dari tatalaksana antikoagulan perioperatif. Tinjauan pustaka ini bertujuan memberikan pendekatan praktis tentang tatalaksana antitrombotik perioperatif yang dapat dipakai dalam praktik klinis sehari-hari.